Massacre in Malaya exposing Britain's My Lai - Hale, Christopher (The History Press, 2013)
The Malayan Emergency (1948-1960) was the longest war fought by British and Commonwealth forces in the 20th century. Today this "war without a name" is largely forgotten, though it had a powerful and secret influence on American strategy in Vietnam.